Evaluation fo the Implementation of the Domestic Component Level Policy on Construction Projects in Indonesia: Case Study of Indoor Multifunction Stadium in Jakarta - Melkysedek, Hobert Mangatur; Pontan, Darmawan; Zaki, Muhammad; Kusumawati, Lili (Journal La Multiapp, 2024)
This research evaluates the implementation of the Domestic Component Level (TKDN) regulation in the Indoor Multifunction Stadium Construction Project in Jakarta to support national economic growth by increasing the use of local products in construction projects. The objectives of this study are to determine the percentage of domestic component use, identify factors that influence the implementation of TKDN, and analyze the main challenges in implementing the policy. The research method involved project and survey data analysis, with the Relative Importance Index (RII) method to assess the dominant factors that play a role in the implementation of TKDN. The results showed that the percentage of local product contribution in this project was 55.80% with a target achievement in accordance with the regulation of 60% with the dominant constraint factor being local product certification. This research is expected to support the TKDN policy on construction projects in Indonesia, strengthen the involvement of domestic industries, and provide input for policymakers to improve the effectiveness of the implementation of this policy.